USE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS FOR THE TREATMENT OF AXIAL SPONDYLOARTHRITIS, INCLUDING ANKYLOSING SPONDYLITIS, MONITORING THEIR EFFICACY AND SAFETY (DRAFT GUIDELINES OF THE EXPERT SPONDYLOARTHRITIS DIAGNOSIS AND TREATMENT GROUP) - I. Z. Gaidukova; A. P. Rebrov; E. N. Otteva; V. V. Badokin; A. G. Bochkova; O. V. Bugrova; A. A. Godzenko; A. A. Dubikov; T. V. Dubinina; O. N. Ivanova; T. V. Korotaeva; S. A. Lapshina; et al. (Научно-практическая ревматология, 2016)
The paper gives the draft guidelines elaborated  by the Expert Spondyloarthritis  Diagnosis and Treatment Group  by order of the Association of Rheumatologists  of Russia. The guidelines include the essentials of how to use nonsteroidal  anti-inflammatory drugs in axial spondyloarthrititides, including ankylosing spondylitis, contain  instructions  for how long they should be administered, and describe possible patient  management tactics in the most common  clinical situations and a preferential  algorithm for evaluating the efficiency and safety of treatment.